Adaptability Through Dynamic Capabilities How Management Can Recognize Opportunities and Threats - Endres, Herbert (Springer Fachmedien Wiesbaden : Gabler, 2018)
This book discusses theories and frameworks addressing the adaptability and sustainable competitive advantages of firms, including dynamic capabilities. This work develops and examines a concept that makes dynamic capabilities more tangible and provides guidance to managers and researchers on how to develop and maintain sustainable competitiveness. The focus thereby lies on sensing, i.e., the capability of firms to recognize opportunities and threats in their environment, and its effect on a firm's financial success. The insights from this work will shift managers' attention from the more static resource-based view to the dynamic capabilities perspective on firms. Contents • Frameworks and Theories addressing Adaptability and Sustainable Competitive Advantages • The Dynamic Capabilities Framework - How firms can survive • The Sensing Capability - How to recognize opportunities and threats Target Groups • Researchers and students in the field of entrepreneurship, strategic management, innovation management, organizational behavior, and marketing • Directors, marketing managers, business consultants and analysts, strategy developers and market researchers The Author Dr. Herbert Endres, MBA is Assistant Professor (Akademischer Rat) for Marketing and Management at the Faculty of Business, Economics, and Management Information Systems, University of Regensburg. Before he started his PhD, he had worked in leading marketing and management positions in the industry.